Language Learning Strategies: Classification and Pedagogical Implication - Ag. Bambang Setiyadi (TEFLIN, 2001)
Many studies have been conducted to explore language learning strategies (Rubin, 1975, Naiman et . al ., 1978; Fillmore, 1979; OMalley et . al ., 1985 and 1990; Politzer and Groarty, 1985; Prokop, 1989; Oxford, 1990; and Wenden, 1991). In the current study a total of 79 university students participating in a 3 month English course participated. This study attempted to explore what language learning strategies successful learners used and to what extent the strategies contributed to success in learning English in Indonesia . Factor analyses, accounting for 62.1 %, 56.0 %, 41.1 %, and 43.5 % of the varience of speaking, listening, reading and writing measures in the language learning strategy questionnaire, suggested that the questionnaire constituted three constructs. The three constructs were named metacognitive strategies, deep level cognitive and surface level cognitive strategies. Regression analyses, performed using scales based on these factors revealed significant main effects for the use of the language learning strategies in learning English, constituting 43 % of the varience in the posttest English achievement scores. An analysis of varience of the gain scores of the highest, middle, and the lowest groups of performers suggested a greater use of metacognitive strategies among successful learners and a greater use of surface level cognitive strategies among unsuccessful learners. Implications for the classroom and future research are also discussed.